Modeling and Simulation to Support Phase Ib/IIa Dose Selection for WBP216, A Long Half-Life Fully Human Monoclonal Antibody Against Interleukin-6 - Xiange Tang; Xiange Tang; Xiaofeng Zeng; Xiaoduo Guan; Xiaoduo Guan; Rui Chen; Rui Chen; Pei Hu; Pei Hu (Frontiers Media S.A., 2021)
WBP216 is an innovative IL-6 antibody, presenting high affinity to IL-6 and a long half-life (40-60 days). To optimize the dosage regimen for future clinical trials, pharmacokinetics (PK) and pharmacodynamics (PD) of WBP216 would be firstly characterized in Chinese rheumatoid arthritis (RA) patients. PK, CRP and DAS28 data of WBP216 were collected from 26 RA patients in a single ascending dose study. Non-linear mixed effects modeling was used for a population PK/PD analysis. A two-compartment model with a sequential zero-first order absorption and a first order elimination best described PK behavior of WBP216. Apparent systemic clearance was 0.015 L/h, central volume was 8.04 L. CRP as the fast-decreasing endpoint and DAS28 as the slow-reacting endpoint were both fitted well through an indirect response model. The baseline of ALT and free IL-6 were found associated with PK/PD parameters during covariates exploration. Simulation results confirmed that a loading dose regimen either of administration at weeks 0, 2, and 6 or doubling the maintenance dose level, followed by maintenance dosing of 75-150 mg every 8 weeks, was expected to provide a best risk/benefit ratio in future clinical studies. We hope this first PK/PD study of WBP216 in Chinese RA patients will help in the clinical development of WBP216 in future and provide a reference to the dosage optimization of similar antibodies with long half-life.Clinical Trial Registration:CTR20170306